Bangunan Trilogi Epistemologi dalam Integrasi Ilmu Abid Al Jabiri - Qoyyim, Moh (MAN 1 Kota Kediri, 2024)
The main theories of science, whether rationalism or empiricism, are developing rapidly in the West. In contrast the wealth of Islamic scholarship which is stagnant due to differences of opinion regarding the dominant source of knowledge originating from dogmatic textuality which is growing rapidly in the Islamic world. The epistemology of Bayani, Burhani, and Irfani is defined by Abid Al Jabiri as Arabic reasoning which is in conflict with each other and sometimes one domain of epistemology is more dominant than another. The unity of these three epistemologies is expected to be a balanced source in the development of science and provide a conceptual framework that enables a more holistic and interdisciplinary integration of science, stimulating cooperation between scientific fields to achieve a deeper understanding of the complexity of reality in the modern Islamic world. Keywords: Trilogy of Epistemology, Integration of Science, Abid Al Jabiri